Evaluation of the remineralization potential of amorphous calcium phosphate and fluoride containing pit and fissure sealants using scanning electron microscopy - Prashant Choudhary; Shobha Tandon; M Ganesh; Anshul Mehra (Wolters Kluwer Medknow Publications, 2012)
Aim: To evaluate the remineralization potential of Amorphous Calcium Phosphate (ACP) and Fluoride containing pit and Fissure Sealants using Scanning Electron Microscopy. Materials and Methods: Thirty maxillary first premolars were divided into three groups of ten each and were randomly selected for ACP containing (Aegis- Opaque White, Bosworth Co. Ltd.), Fluoride containing (Teethmate F1 Natural Clear, Kuraray Co. Ltd.), resin based (Concise- Opaque White, 3M ESPE Co. Ltd.) pit and fissure sealant applications. The Concise group served as a control. The teeth weresubjected to the pH-cycling regimen for a period of two weeks. After two weeks, the teeth were sectioned bucco-lingually into 4mm sections and were observed under Scanning Electron Microscope at 50X, 250X, 500X, 1000X and 1500X magnifications. The qualitative changes at the tooth surface and sealant interface were examined and presence of white zone at the interface was considered positive for remineralization. Results: Both ACP containing (Aegis) and Fluoride containing (Teethmate F1) group showed white zone at the tooth surface-sealant interface. The resin based group (Concise) showed regular interface between the sealant and the tooth structure, but no clear cut white zone was observed. Conclusion: Both, Aegis and Teethmate F1 have the potential to remineralize. Release of Amorphous Calcium Phosphate molecules in Aegis group and formation of Fluoroapetite in Teethmate F1 group, were probably responsible for the remineralization.